Trends In Developing Country Trade 1980-2010 - Michalopoulos, Constantine; Ng, Francis (World Bank, Washington, DC, 2013)
This paper reviews trends and patterns in developing countries' trade from 1980 to 2010. During the 30-year span, world trade expanded rapidly, especially in developing countries in the last decade. A similar picture emerges in trade in services. These overall trends, however, mask different trade patterns during some of the time periods and among different developing countries and groups. For example, except for Asia, the 1980s were pretty much a "lost" decade for many developing countries and groups. But that changed in the 1990s and 2000s, with trade by all major developing countries growing faster than developed countries. From 1980 to 2000, trade by Least Developed Countries grew much more slowly than that of developing countries as a whole. But those countries saw the fastest growth in trade in the following decade. This strong overall trade performance -- with some exceptions (for example Sub-Sahara Africa in the manufacturing trade) -- raises questions about sustainability, trade policy and the architecture of the trading system.